An emerging grounded theory for preaching on poverty in South Africa with Matthew 25:31-46 as sermon text - H. J. C. Pieterse (Acta Theologica)
Since 2009, I am researching sermons on Matthew 25:31-46 by preachers of the Uniting Reformed Church and the Dutch Reformed Church (Nederduitse Gereformeerde Kerk). The sermons are collected in South Africa’s eight provinces. This is an empirical-homiletic study with a grounded theory methodology. The open coding and selective coding cycles are already completed. This article presents the results of the last cycle, namely theoretical coding. The theory for practice describes the concepts which emerged from the data and shows the relationships between the concepts. This is a theory for the practice of preaching on Matthew 25:31-46 in the South African context of poverty. It has a bearing only on the qualitative analysis of the texts of the sermons on this text in Matthew, and does not address the entire process of the preaching event from the sermon text, the rhetorical and communicative process. It only covers the sermon analyses and the effects on the listeners’ actions on the sermons mentioned in the sermons.